Crocin alleviates neuronal arborization damage in the basolateral nucleus of the amygdala and dentate gyrus of the hippocampus in a stressed rat - Kargar Barzi, Mohammadali; Jalali Kondori, Bahman; Meftahi, Gholam Hossein (IBRO neuroscience reports, 2025)
The goal of this research was to explore how crocin can protect neurons in the amygdala and hippocampus, as well as measure its impact on oxidant capacity during chronic immobilization stress in male rats. A group of 24 male Wistar rats, each weighing between 200 and 250 g, were chosen for the study. In a random selection process, the animals were divided into three distinct groups: control, stress, and stress + crocin. For two weeks straight, both the subjects in the stress group and those in the stress + crocin group were subjected to immobilization stress sessions lasting 2 h each day. Thirty milligrams per kilogram of crocin were administered daily to the animals in the stress + crocin group. One day after stress, the morphology of neurons in the hippocampus and amygdala was examined using the Golgi-Cox staining technique. The ELISA kit was utilized for determining the total antioxidant capacity (TAC) and the total oxidant status (TOS). In the dentate gyrus of the hippocampus, as well as the basolateral and central nuclei of the amygdala, there was a significant reduction in dendritic arborizations following chronic immobilization stress. Treatment with Crocin effectively repaired dendritic arborization in both the basolateral nuclei in the amygdala and the dentate gyrus of the hippocampus. Immobilization stress significantly reduced TAC and increased TOS, and crocin administration in stressed rats increased TAC levels and reduced TOS. These results emphasize the neuroprotective and antioxidant potential of crocin in reducing the harmful effects of chronic stress.